Potential drug interactions in surgical patients at a university hospital (Research, Society and Development, 2022)
This study aimed to identify, classify and quantify the potential for drug interactions in patients admitted to a surgical unit. This is a cross-sectional and retrospective study carried out at the surgical clinic of the Neuromuscular System Unit of the Getúlio Vargas University Hospital, located in Amazonas, from August to December 2019. In total, one hundred and ninety-six surgical patients were included in the study.  There was a predominance of females (61.22%), the mean age of the patients was 49.7 ± 15.6 years, with a mean length of stay of 7.2 ± 10.1 days. It was observed that potential drug interactions occurred in one hundred and fifty-two patients (77.55%), with a mean of 3.4 ± 4.0 interactions per patient, totaling six hundred and fifty-nine potential interactions. According to our results, it appears that the role of the clinical pharmacist is important to prevent, detect and manage these possible interactions in surgical units, resulting in the optimization of pharmacological treatment and the improvement of care provided to patients.